Principles of choice of revisional bariatric procedures (review of the literature) - Yu. I. Yashkov; Yu. I. Sedletskiy; D. I. Vasilevskiy; B. Y. Tsvetkov; A. A. Krichmar (Вестник хирургии имени И.И. Грекова, 2020)
Bariatric (metabolic) surgery is currently considered as the most effective treatment for obesity with its comorbidities and metabolic disorders like Diabetes Mellitus type 2. Due to life-long nature of obesity, high rate of its recidivism and increasing number of bariatric/ metabolic operations performing worldwide, the problem of revisional bariatric surgery is becoming extremely actual. The article based on literature data and author's own experience overlooks possible solutions for choice of revisional operations depending on kind of primary bariatric procedure, causes of revision: weight regain, complications and side effects of the primary operation.